Mission in Covid and Post-Covid times in Germany - Vellguth, Klaus (Studia Theologica Varsaviensia, 2022)
The presented aspects are divided into four parts: In a first step, I will take a general look at the course of the pandemic in Germany. In a second step, I will show what role the church played during the months of the pandemic. In a third step, I address pastoral observations on the mission of the church in Germany in times of the pandemic. And in a fourth step, I show what challenges the mission or pastoral care of the church in Germany faces after the pandemic.